POWER IN THE DISCOURSE OF WEST SUMATERA PROVINCE REGIONAL REGULATION NUMBER 7 OF 2018 CONCERNING NAGARI - Sailal Arimi; Elly Delfia (Curricula: Journal of Teaching and Learning, 2024)
This paper is a study of power in West Sumatra Provincial Regulation Number 7 of 2018 about Nagari which is analyzed by using van Dijk's critical discourse analysis (CDA), particularly the analysis of text structures. This critical discourse analysis study of the West Sumatra Provincial Regulation is descriptive qualitative by using observational method. The analysis of critical studies aims to see the hidden power behind the text of Regulation Number 7 of 2018 about Nagari which functions to assist and manage Nagari Government in West Sumatra. Critical discourse analysis of the regional regulation text is included in one of 9 (nine) interesting studies in the development of critical discourse analysis which is known as an institutional discourse because the regulation is a legal product issued by the West Sumatra Provincial Government as institution. Based on the results of the analysis, found power related to domination, ideology, and discrimination against Nagari society in West Sumatra. This research has an implication on the implementation of existing policies in Nagari society. The government as the ruling party fully regulates the Nagari community as an object without providing space to express thoughts and opinions. Likewise, the numbering order for defining Bundo Kanduang in article 1 of the general provisions in the Nagari Regional Regulation is located last and has indications of discrimination. The numbering has an impact on the role of Bundo Kanduang which is not a priority in West Sumatran society which adheres to the matrilineal system (maternal lineage).